COLLECTIVE INVESTMENT IN REAL ESTATE: REITS UNDER THE SEBI – A LEGAL FRAMEWORK - Singh, Anil; Venkateshwarlu N (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Real Estate Investment Trusts or REITs have become an important tool in India capital markets enabling investors to invest in real estate as an asset class in India without holding a property directly. REITs are simplified form of Collective Investment Schemes (CIS) and are regulated by the Securities and Exchange Board of India (SEBI). The purpose of this paper is to discuss the legal status of REITs in India, the reason for treating them as CIS and other issues including transparency, investor protection and development of real estate. In 2014, Securities Exchange Board of India (SEBI) introduced the REIT Regulations, 2014, which brought a major change in the regulation to institutionalize real estate investment without compromising investor interests. The following study examines the regulation, qualifications, compliance and investor rights under the REIT framework. Finally, it demonstrates the commonalities as well as the differences between CIS and REITs, and provides insight into the developing case law on collective investment schemes. The paper also delves into the challenges of implementation, such as tax inefficiencies, a liquidity trap, and the need for more respondents in the broader market. In essence, REITs, under the aegis of erstwhile SEBI regulation, represents the next logical step in the evolution of the principles underpinning CIS adapted to provide considerable benefits stemming from growth in the real estate sector us and offer Indian’s access to investment opportunities not previously available in their own country.